Effects of essential oils supplementation, associated or not with amylase, on dry matter intake, productive performance, and nitrogen metabolism of dairy cows - Silva, A. S. [UNESP]; Cortinhas, C. S.; Acedo, T. S.; Lopes, F. C.F.; Arrigoni, M. B. [UNESP]; Tomich, T. R.; Pereira, L. G.R.; Ferreira, M. H.; Jaguaribe, T. L.; Weber, C. T.; Morenz, M. J.F. (Elsevier, 2023)
The aim was to evaluate the effects of essential oils supplementation, associated or not with amylase, on productive performance, milk fatty acid composition, purine derivatives, ruminal microbial synthesis, and feeding behavior of lactating dairy cows. Thirty-three Holstein dairy cows were blocked by days in milk (78.0 ± 9.51) and allocated according to the milk yield into the treatments: i) no feed additives (CTRL); ii) essential oils (EO), the addition of a blend of essential oils [100 mg/kg dry matter (DM) basis]; and iii) essential oils + amylase (EOam), a combination of essential oils and α-amylase (625 mg/kg DM; provided to achieve 375 KNU/kg of DM). Diets were formulated to requirements supply of 32.0 kg/d and 20.0 kg/d of milk yield and dry matter intake (DMI), respectively, and contained 298 g/kg NDF; 172 g/kg CP, and 282 g/kg starch; DM basis. Cows were adapted to the experimental diets for 14 days and the measurements lasted 56 days. Cows were milked twice daily, and milk samples were collected three times per week in two sequential milkings, to determine fat, protein, lactose, and urea nitrogen contents. The statistical model considered the fixed effects of diet, the week of the measurement period and its interaction, and the random effect of the block. The feed additive supplementation did not affect the DMI (23.9 kg/d). The EOam treatment increased feed efficiency (1.40) compared with CTRL and EO, but there were no differences between CTRL (1.27) and EO (1.21). The inclusion of feed additives did not increase the plasma glucose concentration. EOam increased the milk yield compared to the CTRL (32.2 vs. 28.7 kg/d, respectively). Although, energy-corrected milk (ECM) was not influenced by feed additives. There were no differences for fat (37.4 g/kg), lactose (45.6 g/kg), and milk urea nitrogen contents (17.3 mg/dL). However, cows fed EO had higher milk protein concentration than EOam-fed cows. The use of essential oils associated with amylase increases the milk yield, but not energy-corrected milk yield; it improves the feed efficiency in Holstein dairy cows in mid-lactation, and shifts some ruminal patterns that slightly change the milk fatty acid profile and feeding behavior.
Keywords: Dairy cows; Feed additives; Milk fat; Milk protein; Milk yield